2018
DOI: 10.1111/eva.12676
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of environmental selection despite near‐panmixia in summer flounder

Abstract: Rapid environmental change is altering the selective pressures experienced by marine species. While adaptation to local environmental conditions depends on a balance between dispersal and natural selection across the seascape, the spatial scale of adaptation and the relative importance of mechanisms maintaining adaptation in the ocean are not well understood. Here, using population assignment tests, Approximate Bayesian Computation (ABC), and genome scans with double‐digest restriction‐site associated DNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 112 publications
(119 reference statements)
5
37
1
Order By: Relevance
“…Despite these advancements, delineating discrete conservation units can still be problematic. For example, taxonomic uncertainty can lead to confusion regarding species boundaries (Bickford et al, 2007;Hey, Waples, Arnold, Butlin, & Harrison, 2003), and observed phenotypic, spatial, temporal, or behavioral differences can be opposed by apparent genetic panmixia (Als et al, 2011;Hoey & Pinsky, 2018;Palm, Dannewitz, Prestegaard, & Wickström, 2009). Perhaps no other group embodies the challenges of defining conservation units better than the coregonines.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advancements, delineating discrete conservation units can still be problematic. For example, taxonomic uncertainty can lead to confusion regarding species boundaries (Bickford et al, 2007;Hey, Waples, Arnold, Butlin, & Harrison, 2003), and observed phenotypic, spatial, temporal, or behavioral differences can be opposed by apparent genetic panmixia (Als et al, 2011;Hoey & Pinsky, 2018;Palm, Dannewitz, Prestegaard, & Wickström, 2009). Perhaps no other group embodies the challenges of defining conservation units better than the coregonines.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs produced from high-throughput sequencing have led to the identification of previously undetected population structure in a number of marine and terrestrial species K E Y W O R D S connectivity, genotype-by-sequencing, management recommendations, Olympia oyster, outlier loci, population genomics (Everett et al, 2016;Reitzel, Herrera, Layden, Martindale, & Shank, 2013;Van Wyngaarden et al, 2016). Compared to the Atlantic coast of North America (Hoey & Pinsky, 2018), studies utilizing genomewide SNPs for marine taxa from the Pacific coast are far fewer in number and have been limited to regional spatial scales (De Wit & Palumbi, 2013;Drinan et al, 2018;Gleason & Burton, 2016;Larson et al, 2014;Martinez, Buonaccorsi, Hyde, & Aguilar, 2017) or in the number of sampling sites (Pespeni, Oliver, Manier, & Palumbi, 2010;Tepolt & Palumbi, 2015). This study is the first of my knowledge to utilize thousands of SNPs to extensively survey the rangewide population structure of a marine species along this coast.…”
Section: Introductionmentioning
confidence: 99%
“…Dempster, 1955;Kawecki and Ebert, 2004;Levene, 1953;Ravigné et al, 2004;Scheiner, 1993). Local adaptation is expected to evolve in populations with limited connectivity, but if environmentally driven selection is strong enough, adaptive differentiation can still accumulate despite ongoing gene flow (Feder et al, 2012;Hoey and Pinsky, 2018). In the marine environment, reproduction via broadcast spawning and gamete mixing at the sea surface favor the dispersal potential (i.e.…”
Section: Introductionmentioning
confidence: 99%